Perlindungan Hukum Rumah Secound Melalui Devlover Property Atas Pembatalan Sepihak Kesepakatan oleh Penjual ditinjau dari Undang-undang No.8 tahun 1999 Tentang Perlindungan Konsumen - Afendy, Kosim; Litoama, Fransiskus (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
An agreement is an agreement, either written or oral, made by two or more parties, in which both parties agree to obey what is stated in the agreement. In article 1313 of the Civil Code, an agreement is an action by one or more people that binds themselves to one or more people. One of the problems in buying and selling used houses is the legal act of buying and selling which is often carried out by the public where the buying and selling involves a legal relationship between the seller and the buyer who are bound to each other. There are many objects of buying and selling, one of which is buying and selling used houses. . Unlawful acts are also regulated in the Civil Code, which explains that every unlawful act that causes harm to another person requires that the person whose fault caused the loss is obliged to compensate for that loss.